2014
DOI: 10.1016/j.ijadhadh.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Adherend thickness effect on the tensile fracture toughness of a structural adhesive using an optical data acquisition method

Abstract: Adhesive bonding is nowadays a serious candidate to replace methods such as fastening or riveting, because of attractive mechanical properties. As a result, adhesives are being increasingly used in industries such as the automotive, aerospace and construction. Thus, it is highly important to predict the strength of bonded joints to assess the feasibility of joining during the fabrication process of components (e.g. due to complex geometries) or for repairing purposes. This work studies the tensile behaviour of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…9 Some work has been done on the study of how specific geometric parameters influence the resulting fracture toughness (G IC ). An increasing trend of G IC with adherend thickness was found, 10 which is relevant to our study on DCB size reduction. This behaviour was considered to be due to an increasing degree of adherend restraining for bigger thickness values, as a larger region is loaded ahead of the crack tip.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…9 Some work has been done on the study of how specific geometric parameters influence the resulting fracture toughness (G IC ). An increasing trend of G IC with adherend thickness was found, 10 which is relevant to our study on DCB size reduction. This behaviour was considered to be due to an increasing degree of adherend restraining for bigger thickness values, as a larger region is loaded ahead of the crack tip.…”
Section: Introductionsupporting
confidence: 70%
“…All these geometric parameters may have an effect on the values of fracture toughness, because it has been suggested that G IC is not a material parameter, but a geometry-dependent quantity instead. 10 Furthermore, all these parameters are used in the CBBM data reduction scheme, suggesting they influence the end values. 17 Initial crack length.…”
Section: Effect Of Variations On the Geometry Of The Dcb Specimensmentioning
confidence: 99%
“…In spite of the above questions regarding the meaningfulness of the mode I fracture energy, the DCB specimen has been increasingly used to evaluate the traction-separation law of the adhesive [17][18][19][20][21][22][23][24][25]. The method employed, often designated as "direct", reqAccurate methods to compute J I , which may in turn require measurements of load-point crack-tip rotations [19,20,25], or simply application of beam theory based data reduction schemes [21][22][23][24] similar to those used for delamination of composites [16,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The method employed, often designated as "direct", reqAccurate methods to compute J I , which may in turn require measurements of load-point crack-tip rotations [19,20,25], or simply application of beam theory based data reduction schemes [21][22][23][24] similar to those used for delamination of composites [16,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Campilho et al studied the influence of adherend thickness on the measured value of G Ic of a ductile adhesive through DCB tests. Regardless of the data reduction methods, a growing trend of G IC regarding the thickness has been found, suggesting that the G Ic is not a material parameter, but it is a parameter dependent on the geometry used [13]. Moreover, in thin-layer adhesive joints, cracks are forced to follow the defined path through the middle area, since in general the adhesive is weaker and more adaptable than the substrates, which usually causes a cohesive failure of the adhesive [14].…”
mentioning
confidence: 99%